Discrete element modeling of rock-concrete bi-material discs under dynamic tensile loading. (11th April 2022) - Wang, Lu; Wang, Luqi; Yang, Yang; Zhu, Xing; Zhang, Dong; Gao, Xuecheng
Highlights: A 2D split Hopkinson pressure bar (SHPB) system was established using the discrete element method (DEM) to study the dynamic response of the bi-material rock-concrete disc. The varied parameters of the bi-material specimens included rock type, interface inclination, and specimen configuration. The progressive cracking of the bi-material specimens was studied to further reveal the failure pattern. The moment tensor inversion based on the recognition of the acoustic emmsion (AE) event revealed the micromechanical behaviors of the bi-material specimens. Abstract: As the most fragile component in a bi-material, the performance of the rock-concrete interface can greatly affect the stability and durability of the concrete structures founded on the rock masses. In this study, a range of numerical simulations using the discrete element method (DEM) have been conducted to identify the failure mechanism and mechanical property of the rock-concrete bi-materials under the dynamic flattened Brazilian disc (FBD) tests using the modeled split Hopkinson pressure bar (SHPB) system. There are four groups of bi-material specimens that differ in the aspects of rock type (i.e. limestone and sandstone), interface inclination (i.e. 0°, 15°, 30°, 45°, 60°, 75°, and 90°), and specimen configuration (i.e. intact and hollow). The numerical results show that the nominal tensile strength depends on the rock type, and the intact specimen has a higher loading capacity than that of the hollow specimen. The failure modes are classified into three main types in intact limestone-concrete bi-materials according to the degree of the interface angle, which is in good agreement with the previous experimental results. Such transition from interface failure to tensile failure can be observed as well in the bi-material specimens with a hole inside, while the varying inclination angle has a minimal effect on the failure pattern of the sandstone-concrete bi-material specimens. The cracking process of the specimens is visualized using the evolution of acoustic emission (AE) activities. The moment tensor inversion interprets that more energy is required for cracks to propagate from concrete to limestone. The overall AE magnitude is the lowest in limestone-concrete specimens with a pre-cut opening due to the deteriorated specimen bearing capacity.